English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Let x = 1.
Therefore,
x^5 = 1

Transpose
x^5 - 1 = 0

Factor
(x - 1)(x^4 + x³ + x² + x + 1) = 0

Divide by x - 1
x^4 + x³ + x² + x + 1 = 0

Now, since x = 1 (from above)
1^4 + 1³ + 1² + 1 + 1 = 0

Therefore,
1 + 1 + 1 + 1 + 1 = 0

therefore,
5 = 0

What happened?
^_^

...easy...

2006-12-08 21:40:26 · 8 answers · asked by kevin! 5 in Science & Mathematics Mathematics

8 answers

Hmmm..u factorise correctly? it seem so complicated....
if it is correct, then it is probably a trick then.....magic.lol
5=0?
i dunno....

2006-12-08 22:01:18 · answer #1 · answered by turtl3e 2 · 0 1

you are wrong in the part

Factor
(x - 1)(x^4 + x³ + x² + x + 1) = 0

Divide by x - 1
x^4 + x³ + x² + x + 1 = 0 since x = 1 the term x - 1

signifies 1 - 1 or 0 then you've divided it from 0

and zero divided by zero is indeterminate so there's no
particular answer to that question.

2006-12-08 23:25:52 · answer #2 · answered by jdash01 3 · 0 0

U divided by (x-1).since x=1 (x-1)=0. u cannot divide any no. by zero, so that was the mistake.
(x-1)(x^4+x^3+x^2+x+1)=0 means either x=1 or the other factor equals zero not both at the same time

2006-12-08 21:54:52 · answer #3 · answered by jack 1 · 1 0

Aha !
You say that x = 1 ?
And then you divide by x-1, which is equal to 0 ?
Dividing by 0 is not allowed

2006-12-08 21:50:10 · answer #4 · answered by Longfellow 3 · 2 0

look at x ---> a million/(2+x). It decays on R+ and its spinoff is continuously lower than a million/4 in absolute fee. The fastened element L is given with techniques from L(2+L) = a million so L = sqrt(2) - a million. for this reason (x_(n+a million)-L) = f'(c) (x_n - L) for some c between L and x_n; hence |x_(n+a million) - L| < a million/4 |x_n - L|. So the sequence (x_n) converges in the route of L and the version decays faster than (a million/4)^n

2016-11-30 08:39:56 · answer #5 · answered by ? 4 · 0 0

The power of equation means how many solutions you can find; thus x-1=0 means single solution, i.e. x=1,
And x^5=1 means 5 solutions.
Now as j=sqrt(-1) and 1 = e^(2pi*k*j) = cos(2pi*k) + j*sin(2pi*k),

let’s consider x^5=e^(2pi*k*j), hence x=e^(2pi*k*j/5),
where k=-1,-2,0,1,2; and
x1=cos(0.4pi)-j*sin(0.4pi),
x2=cos(0.8pi)-j*sin(0.8pi),
x3=1;
x4=cos(0.4pi)+j*sin(0.4pi),
x5=cos(0.8pi)+j*sin(0.8pi);
x=1 by the way is only 1 of 5 possible solutions!

2006-12-09 02:43:18 · answer #6 · answered by Anonymous · 0 0

Can't divide through by (x-1) since you cannot divide by zero.

Steve

2006-12-08 21:50:09 · answer #7 · answered by Anonymous · 2 0

i like what longfellow said, stops you right in your tracks easily

2006-12-08 21:52:38 · answer #8 · answered by J Balla 4 · 0 0

fedest.com, questions and answers